Security Agent Location in the Internet of Things - Ioannou, Christiana; Vassiliou, Vasos (IEEE access, 2019)
The Internet of Things (IoT) provides the ability to extend the Internet into devices and everyday objects, in a way that they are uniquely addressable. Sensors, actuators, as well as everyday devices and objects, such as cellphones, cars, and homes, are interconnected and form a network that can be accessed, monitored, and controlled remotely. Security is an important subject in the IoT networks since the devices and the networks can be used as a means of invading the users' privacy. The current work examines the issue of security agent location using indicative intrusion detection techniques for network layer attacks. We analyze the methodology, operation, as well as the complexity of each technique. Through the extensive implementation and experimentation, we are able to conclude that the local security agents have the same performance results with centralized and decentralized approaches, but with negligible overhead. As such, they are useful when internal network communication, or network augmentation with monitoring nodes, is not feasible.